2016
DOI: 10.4097/kjae.2016.69.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electromagnetic guidance system on early learning curve of ultrasound for novices

Abstract: BackgroundElectromagnetic guidance reveals needle alignment and position relative to the image plane on an ultrasound view. This study compared the early learning curves of novices performing ultrasound-guided needle placement with (n = 10) or without electromagnetic guidance (n = 10).MethodsParticipants performed 30 ultrasound-guided needle placements using an echogenic stick (0.3-cm diameter) as a target inside a phantom model; this early learning period was divided into sequential periods (P1: 1–5, P2: 6–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…) . Inexperienced participants using the Ezono 4000 (Ezono AG, Jena, Germany) needed fewer out‐of‐plane attempts, shorter procedure times and made significantly less posterior wall and carotid artery punctures in simulated internal jugular vein cannulation . A recently developed prototype by General Electric (Wisconsin, USA) uses passive magnetic characteristics of commercially available needles, omitting the magnetisation procedure and, thus, improving workflow.…”
Section: Resultsmentioning
confidence: 99%
“…) . Inexperienced participants using the Ezono 4000 (Ezono AG, Jena, Germany) needed fewer out‐of‐plane attempts, shorter procedure times and made significantly less posterior wall and carotid artery punctures in simulated internal jugular vein cannulation . A recently developed prototype by General Electric (Wisconsin, USA) uses passive magnetic characteristics of commercially available needles, omitting the magnetisation procedure and, thus, improving workflow.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies involving these devices and others, including the SonixGPS (UltraSonix, Richmond, BC, Canada) and Venue 50 (GE Healthcare, Chicago, IL, USA), have been pre-clinical in nature. [12][13][14][15][16][17] Two randomized studies using the SCENERGY and eZono 4000 (eZono, Jena, Germany) devices demonstrated 100% successful cannulation and no complications in use with adult patients; however, only the former showed a time-savings benefit 10,18 . Prior to this report, no such device has been studied in, specifically, the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of UALP with NGS could help overcome inexperience and lack of confidence in situations where LP is not performed routinely. It could also serve as an important teaching tool by helping novices to gain a deeper knowledge of spinal anatomy, as well as to gather experience, handling-skills and self-confidence[ 12 , 14 , 39 ]. Finally, UALP with NGS could serve to either complement—or even replace—fluoroscopically-guided lumbar puncture in difficult LP cases, including those in previously-operated or elderly patients with inflexible spines or difficult landmarks, or in ventilated ICU patients in the prone position.…”
Section: Discussionmentioning
confidence: 99%